Características da arborização na região central do município de Coxim/MS - Mota, Mariana Pereira; Almeida, Luiz Fernando Rolim de [UNESP] (My University, 2011)
Urban forest plays a role of vital importance for quality of life in urban centers. Due to its multiple functions, urban forest acts directly on urban climate, air quality, level of noise and also on landscape, besides being essential refuge to remaining wildlife in the cities. Urban tree planting requires careful planning and a proper management to provide benefits. However, many Brazilian cities don’t have this planning, thus many projects are purely based in empirical methods. Was done the analysis of urban forest in the neighborhood of São Judas Tadeu where were found 226 trees with 17 different species showing attacks by insects as termites and ants besides interferences in the power network. The species Caesalpinia peltophoroides and Monquilea tomentosa represent 70% of total species found, but these trees are not suitable for urban forest, bring consequences for the integrity of species and the urban environment. The use of improper species in urban tree planting carries several losses, beyond the risk of accidents to the population, because it requires that the public services providers perform periodic pruning, drastic cuts and even the removal of existing vegetation.

A arborização exerce papel de vital importância para a qualidade de vida nos centros urbanos. Por suas múltiplas funções, a arborização urbana atua diretamente sobre o clima, a qualidade do ar, o nível de ruídos e sobre a paisagem, além de constituir refúgio indispensável à fauna remanescente nas cidades. A arborização urbana exige um planejamento criterioso e um manejo adequado para proporcionar benefícios. Entretanto, muitas cidades brasileiras não possuem tal planejamento, portanto muitos projetos baseiamse em métodos puramente empíricos. Foi feita a análise da arborização urbana do bairro São Judas Tadeu, onde foram encontradas 226 árvores com 17 espécies diferentes apresentando ataques de insetos como cupins e formigas, além de interferências na rede elétrica. As espécies Caesalpinea peltophoroides e Monquilea tomentosa representam 70% do total de espécies encontradas, porém não são árvores indicadas para a arborização urbana trazendo conseqüências para a integridade das espécies e do ambiente urbano. O uso inadequado da arborização acarreta vários prejuízos, além dos riscos de acidentes à população, pois exige que os órgãos prestadores de serviços públicos realizem podas periódicas, cortes drásticos e até mesmo a eliminação da vegetação existente.
Urban forest characteristics in down town of city of Coxim, MS
Keywords: Urban forest; Urban environment; Urban floristic; Coxim; Arborização urbana; Ambiente urbano; Florística urbana; Coxim